2009
DOI: 10.3390/ijms10041514
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Silk Biomaterials

Abstract: Silk fibroin from the silkworm, Bombyx mori, has excellent properties such as biocompatibility, biodegradation, non-toxicity, adsorption properties, etc. As a kind of ideal biomaterial, silk fibroin has been widely used since it was first utilized for sutures a long time ago. The degradation behavior of silk biomaterials is obviously important for medical applications. This article will focus on silk-based biomaterials and review the degradation behaviors of silk materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
459
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(470 citation statements)
references
References 52 publications
4
459
1
6
Order By: Relevance
“…These results demonstrated that the overall enzymatic degradation of the silk component was mediated by surface erosion. [41] To evaluate the effect of enzyme exposure, the electrical resistance was monitored during the incubation period in buffered protease XIV solution or PBS as controls (Figure 8a). The sheet resistivity increased from 0.6 to ~5.4 kΩ sq -1 upon 10 days exposure to the enzyme solution, roughly 9 times compared with its original value.…”
Section: Enzymatic Degradation Of Sf-ppy Filmmentioning
confidence: 99%
“…These results demonstrated that the overall enzymatic degradation of the silk component was mediated by surface erosion. [41] To evaluate the effect of enzyme exposure, the electrical resistance was monitored during the incubation period in buffered protease XIV solution or PBS as controls (Figure 8a). The sheet resistivity increased from 0.6 to ~5.4 kΩ sq -1 upon 10 days exposure to the enzyme solution, roughly 9 times compared with its original value.…”
Section: Enzymatic Degradation Of Sf-ppy Filmmentioning
confidence: 99%
“…Regarding the first assumption, it is known that amorphous regions are easily degraded due to better accessibility of degradation agents such as VOCs, water vapour, oxygen [9][10][11]50], unlike tightly packed crystalline regions. The second assumption has its consequences in the calculation of DP.…”
Section: Kinetics Of Degradationmentioning
confidence: 99%
“…Ordered crystalline regions making up about 60 % of the fibroin mass [6] are interspersed with amorphous regions located in the area of the light chain [7]. These regions are richer in the hydrophilic amino acids such as serine, threonine, arginine and lysine, which are more susceptible to degradation [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…An ideal biomaterial is one that is nonimmunogenic, biocompatible, and biodegradable, which can be functionalized with bioactive proteins and chemicals. In particular, biodegradability is one of the essential properties of the biomaterials [11]. It must be emphasized that the key factors in biomaterial usage are its biocompatibility, biofunctionality, and availability to a lesser extent.…”
Section: Historymentioning
confidence: 99%